Membangun Model Perbankan Syariah yang Transparan, Akuntanbel, Responsibility, Independensi dan Fairness Perspektif Pengetahuan (Survey Pada Perbankan Syariah di Propinsi Jambi) - Mukhzarudfa Mukhzarudfa (Universitas Batanghari, 2019)
Jambi Province is one of the provinces with the largest Muslim population in Indonesia, with such a large population, Jambi Province should have been a pioneer and direction for the development of Islamic banking and finance in Indonesia. Nevertheless, the contribution of sharia business is still very low compared to conventional business, in 2016 the sharia banking market share is still less than 5%. For the development of sharia banking in the future, the specificity of the application of sharia principles in totality, demanding products and contracts of Islamic banking must have a link with real sector activities. This is where an understanding of governance and a professional business model and the aspects of muamalat fiqh are needed. Islamic banking as a modern banking needs to be managed with the principles of modern governance, which are in accordance with sharia principles, for this reason, this study tries to uncover and analyze how the model of sharia corporate governance implementation in sharia financial institutions. This study aims to explore the model of disclosure mechanism of sharia banking corporate governance in Jambi Province. The sample banks in the study consisted of 7 Islamic banks in Jambi Province. Research is done by using Qualitative Methods. Data analysis is done using the content analysis method. The results of the study show that for 2016, the sharia banking model that is transparent, accountable, responsive, independent and fairness analyzed can be grouped into four aspects, namely the regulatory aspects, organizational structure, process aspects and functions. From the aspects analyzed, it can be concluded that the Islamic commercial banks in implementing their governance show that bank management has implemented the principles of governance fairly well, in accordance with the provisions of the applicable legislation. And there are still significant weaknesses in the application of its sharia governance structure model. The sharia governance model that is built is to produce a sharia banking model that is transparent, accountable, responsible, independent and fairness that is applied in Jambi Province at the same time as the provisions that apply to sharia banking internationally.